Spatially constrained hierarchical parcellation of the brain with resting-state fMRI - Blumensath, Thomas; Jbabdi, Saad; Glasser, Matthew F.; Van Essen, David C.; Ugurbil, Kamil; Behrens, Timothy E.J.; Smith, Stephen M. (NeuroImage (Orlando, Fla.), 2013)
We propose a novel computational strategy to partition the cerebral cortex into disjoint, spatially contiguous and functionally homogeneous parcels. The approach exploits spatial dependency in the fluctuations observed with functional Magnetic Resonance Imaging (fMRI) during rest. Single subject parcellations are derived in a two stage procedure in which a set of (~1000 to 5000) stable seeds is grown into an initial detailed parcellation. This parcellation is then further clustered using a hierarchical approach that enforces spatial contiguity of the parcels. A major challenge is the objective evaluation and comparison of different parcellation strategies; here, we use a range of different measures. Our single subject approach allows a subject-specific parcellation of the cortex, which shows high scan-to-scan reproducibility and whose borders delineate clear changes in functional connectivity. Another important measure, on which our approach performs well, is the overlap of parcels with task fMRI derived clusters. Connectivity-derived parcellation borders are less well matched to borders derived from cortical myelination and from cytoarchitectonic atlases, but this may reflect inherent differences in the data. •A novel computational strategy is proposed to partition the cerebral cortex.•Single subject parcellations are derived based on rs-fMRI.•High scan-to-scan reproducibility is found.•Parcel borders delineate clear changes in functional connectivity.•There is a significant overlap of parcels with task fMRI derived clusters.